2009
DOI: 10.1016/j.bpj.2009.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Electrotonic Coupling between Human Atrial Myocytes and Fibroblasts Alters Myocyte Excitability and Repolarization

Abstract: Atrial fibrosis has been implicated in the development and maintenance of atrial arrhythmias, and is characterized by expansion of the extracellular matrix and an increased number of fibroblasts (Fbs). Electrotonic coupling between atrial myocytes and Fbs may contribute to the formation of an arrhythmogenic substrate. However, the role of these cell-cell interactions in the function of both normal and diseased atria remains poorly understood. The goal of this study was to gain mechanistic insight into the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
142
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(163 citation statements)
references
References 34 publications
21
142
0
Order By: Relevance
“…For fibroblasts, previous studies using myocytefibroblast co-culture models have shown that the fibroblasts depolarized electrotonically coupled myocytes (Miragoli et al, 2006;MacCannell et al, 2007;Jacquemet and Henriquez, 2008;Maleckar et al, 2009). Our simulations also showed a depolarizing effect of coupled fibroblasts on the resting membrane potential of ventricular myocytes.…”
Section: Effects Of Fibroblast Coupling On Human Ventricular Myocyte supporting
confidence: 70%
See 1 more Smart Citation
“…For fibroblasts, previous studies using myocytefibroblast co-culture models have shown that the fibroblasts depolarized electrotonically coupled myocytes (Miragoli et al, 2006;MacCannell et al, 2007;Jacquemet and Henriquez, 2008;Maleckar et al, 2009). Our simulations also showed a depolarizing effect of coupled fibroblasts on the resting membrane potential of ventricular myocytes.…”
Section: Effects Of Fibroblast Coupling On Human Ventricular Myocyte supporting
confidence: 70%
“…The main reasons are that: (1) There is lack of experimental data due to the small size of individual fibroblasts ; (2) Ca 2+ current, as a control factor of active tension, has not been identified for membrane ionic currents in fibroblasts Shibukawa et al, 2005;MacCannell et al, 2007;Maleckar et al, 2009). The active force of fibroblasts was therefore ignored at the cellular level in this study.…”
Section: Model Frameworkmentioning
confidence: 99%
“…Other publications like [4], [8], and [7] have also investigated the influence of myocyte-fibroblast coupling in the human atrium. Here, we consider for the first time the differential effects on a heterogeneous set of cellular models representing different regions within the human atria.…”
Section: Discussionmentioning
confidence: 99%
“…The 10 different regions are the right and left atrial working myocardium (RA and LA), the right and left atrial appendage (RAA and LAA), Bachmann's bundle (BB), the crista terminalis (CT), pulmonary veins (PV), the septum (Sep), and the mitral and tricuspid valve ring (MVR and TVR). Each of these model variants were coupled to the human atrial fibroblast model proposed by Maleckar et al [4]. The fibroblast model of type Active 1 was chosen with a resting membrane voltage of -47.8 mV.…”
Section: Methodsmentioning
confidence: 99%
“…Ggap was set to 0.5 nS [1]. Additionally, the number of attached fibroblasts to a single myocyte varied from 0 to [8]. APDs were measured at 90% of repolarization (APD90).…”
Section: Cellular Simulations (0d)mentioning
confidence: 99%